Indeks Kepuasan Masyarakat Terhadap Pelayanan di Perpustakaan Daerah Kabupaten Hulu Sungai Utara - Siti Raudah; Risna Amalia (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This research is motivated by obstacles in fulfilling facilities, the absence of a waiting room in circulation services, the lack of staff, the presence of noise in the reading room area, and the lack of book updates. The purpose of this study is to determine the level of Public Satisfaction with Services at the Hulu Sungai Utara Regency Regional Library. The research method is descriptive quantitative, with a sample of 94 respondents. Data collection techniques are distributing questionnaires, observation, literature studies, and documentation. The sampling technique uses Probability Sampling, analyzing data using the perception value provision test. The results show that the index value obtained is 3.044 and the value of the public satisfaction index after being converted is 76.1, so the service quality is "B". So it can be concluded that the Public Satisfaction Index at the Hulu Sungai Utara Regency Regional Library is said to be good. Then, it can be seen that the indicator that has the highest IKM value is requirements = 3.176 (11.57%) with a conversion value of (3.176 X 25) = 79.4 weight value "B" category Good/Satisfied, while the lowest indicator value is facilities and infrastructure = 2.968 with a conversion value of (2.968 X 25) = 74.2 weight value "C" category Less Good/Less Satisfied. Several aspects that must be made the main priority in improving services are adjusted to the findings in this study, namely completion time, implementer competence, complaint handling, and facilities and infrastructure